2020
DOI: 10.1103/physrevd.101.056008
|View full text |Cite
|
Sign up to set email alerts
|

Into the conformal window: Multirepresentation gauge theories

Abstract: We investigate the conformal window of four-dimensional gauge theories with fermionic matter fields in multiple representations. Of particularly relevant examples are the ultra-violet complete models with fermions in two distinct representations considered in the context of composite Higgs and top partial-compositeness. We first discuss various analytical approaches to unveil the lower edge of the conformal window and their extension to the multiple matter representations. In particular, we argue that the sche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 103 publications
(176 reference statements)
4
34
0
1
Order By: Relevance
“…In a walking theory the dimension of the fermions in eq. (4.3) are lower at Λ U V and then the powers of Λ U V reduce (see for example [26,76] for discussion). Here, though, we will provide a new mechanism that allows an order one top Yukawa coupling as needed for the top mass.…”
Section: Review Of Composite Higgs Modelsmentioning
confidence: 99%
“…In a walking theory the dimension of the fermions in eq. (4.3) are lower at Λ U V and then the powers of Λ U V reduce (see for example [26,76] for discussion). Here, though, we will provide a new mechanism that allows an order one top Yukawa coupling as needed for the top mass.…”
Section: Review Of Composite Higgs Modelsmentioning
confidence: 99%
“…x * 4.2 [9] (see also [10]). Previous analysis based on the perturbative series in the gauge-coupling found n * f ≈ 9 [11,12] for n c = 3, and using the Banks-Zaks conformal expansion found n * f ≈ 10 [13] or n * f ≈ 9 [14] for n c = 3, and x * ≈ 2.9 [14] in the Veneziano limit. 1 Lattice methods are the only ones so far based on first principles.…”
Section: Jhep07(2020)049mentioning
confidence: 95%
“…10 We will then assume in what follows that the conformal series (2.8) and (2.9) are all divergent asymptotic, consistently with our assumption about the coupling expansion. Even if IR renormalons might not occur, 7 Very recently the conformal expansion has been used to study the lower edge of the conformal window [13]. Assuming that γ equals exactly one at the lower edge, it has been found that n * f ≈ 10 in QCD.…”
Section: Banks-zaks Conformal Expansionmentioning
confidence: 99%
See 2 more Smart Citations